PERBUDAKAN DALAM PANDANGAN ISLAM HADITH AND SIRAH NABAWIYYAH: TEXTUAL AND CONTEXTUAL STUDIES - Abdul Hakim Wahid (Universitas Islam Negeri Fatmawati Sukarno, 2015)
This paper proves that the law of slavery in Islam is just steps to abolish slavery gradually and not to legalize it. This paper was written to refute the conclusions Western orientalists, especially Robert Morey who assume that Islam justifies slavery as embodied in the Qur’an and the Prophet’s life history as the basis of false allegations against the Prophet and Islam